Optimization of Fixed Asset Accounting Information Systems in Supporting Asset Management at Bandung City Rusunawa Regional Technical Implementation Unit - Radi Mugisana; Tuntun Ariadi Sukanta (Journal of Innovation and Community Engagement, 2026)
Fixed asset management in the public sector plays an important role in supporting the quality of public services. However, in practice, there are often challenges such as limited human resources, an unfavorable workload, and suboptimal use of digital applications. The purpose of this study is to support the optimization of the fixed asset accounting information system in the technical implementation unit of the Rusunawa in Bandung, through a Participatory Action Research approach with active participation, concrete actions, and simultaneous research in a social context. The contribution of partners is reflected in the provision of data, direct assistance, validation of results, and adoption of the proposed procedures. Data collection techniques included observation, discussion, collaborative participation, and document study through several stages. The preparation stage focused on tidying up the warehouse and creating an adequate layout to facilitate the recording, management, and grouping of fixed assets. The implementation stage focused on inventorying assets in the field to improve the accuracy and currency of data related to location, quantity, and functional condition. The evaluation and reporting stage focuses on preparing recommendations for a fixed asset accounting information system flowchart in the context of inventory and asset procurement for asset maintenance needs. The results of the study provide economic added value in improving the efficiency and effectiveness of budget management for asset procurement or maintenance, while in the social sphere, it improves the quality of service and sustainable public trust.